The Effect of an Asynchronous Course Management System on Learning the Microsoft Office Excel 2003 Program in Tertiary Education - Venardakis Νικόλαος; Zetou Ελένη; Giannousi Μαρία; Antoniou Παναγιώτης; Kioumourtzoglou Ευθύμης (Inquiries in Physical Education and Sport, 2008)
The purpose of this study was to examine the effectiveness of using an asynchronous course management system on learning the Microsoft office Excel 2003 program as a supplement to traditional lecture instruction approach. First year university students (N=163) were randomly assigned into two teaching method groups: traditional lecture instruction (TLI) and combined lecture instruction (CLI). Each group received five 95-min periods of instruction divided into 4 sections: a) 5-min briefly outline of the key learning points, b) 40-min lecture on general knowledge c) 45-min constructivist-inspired learning activities and d) 5-min summary on key learning points. TLI group subjects experienced the Microsoft office Excel 2003 program by an instructor, whereas, the CLI group experienced the same program, through the asynchronous course management system E-Class as well as through the TLI. In the beginning and the end of this study students completed an 18-item multiple choice knowledge test. A two-way analysis of variances (ANOVA), with repeated measures on the last factor, was conducted to determine effect of method groups (TLI, CLI) and measures (pre-test, post-test) on knowledge test. No significant differences between the groups concerning the written test, were found. Conclusively, the use of an asynchronous course management system can be an effective teaching tool on learning spreadsheet programs in combination with TLI method.